2022
DOI: 10.3390/ma15144806
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hydrogen on the Structure and Mechanical Properties of 316L Steel and Inconel 718 Alloy Processed by Selective Laser Melting

Abstract: The interaction of hydrogen with specimens of 316L steel and Inconel 718 alloy processed by selective laser melting (SLM) was studied. The effect of hydrogen on the mechanical properties of SLM materials, hydrogen permeability, and microstructure was investigated; besides, these values were compared with the properties of conventionally produced materials. It was shown that SLM can be successfully used to produce parts for operation in hydrogen environments at high pressure at room temperature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 43 publications
2
4
0
Order By: Relevance
“…The diffusivity calculated from ITDS results shows a good agreement with literature values of wrought Inconel 718 for different metallurgical conditions [45,71], as shown in Fig. 6 and Table 3.…”
Section: Hydrogen Diffusionsupporting
confidence: 83%
See 1 more Smart Citation
“…The diffusivity calculated from ITDS results shows a good agreement with literature values of wrought Inconel 718 for different metallurgical conditions [45,71], as shown in Fig. 6 and Table 3.…”
Section: Hydrogen Diffusionsupporting
confidence: 83%
“…Furthermore, there is a need for (1) a hydrogen trapping assessment in fully saturated samples to gain insight into the nature of the preferential trapping sites that in uence crack initiation and propagation; and (2) a hydrogen diffusivity and uptake assessment for samples with the same thickness as for tensile tests, which will enable correlating HE susceptibility indexes to hydrogen content. Recently Maksimkin et al [45] provided a hydrogen diffusivity value in annealed samples based on gas permeation studies. However, such studies are time-consuming and challenging to perform.…”
Section: Introductionmentioning
confidence: 99%
“…There are two competing factors which affect the HE susceptibility of AM316L SS: the surface roughness and the hydrogen trapping sites [ 19 , 20 , 21 , 22 , 23 , 45 ]. Hydrogen atoms effectively diffuse into the rough surface as the surface flaws and other imperfections, such as pores, serve as entrances for the H atoms, as reported in the literature [ 24 , 44 , 45 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have been conducted on the HE susceptibility of 3D-printed 316L-SS [ 19 , 20 , 21 , 22 , 23 , 24 ]. These studies have found that volumetric defects, sub-grains in the cellular structure, and the melt pool boundaries present in selective laser melted (SLMed) 316L-SS act as potential trapping sites for H atoms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation